Control over the product and the cost of poor quality in the execution of asphalt mixtures - Miró Recasens, Rodrigo (2025)
The determination of indirect tensile strength in bituminous mixtures is a mechanical parameter that can serve as a highly useful tool for evaluating the quality of the construction process of the asphalt layer. It is important to prevent the reduction of this strength, as it directly affects the pavement's in-service performance. At the Roads Laboratory of the Polytechnic University of Catalonia, the potential implementation of the indirect tensile strength test in the quality control of asphalt layer construction has been studied. As a complementary part of this research, the resilient moduli of the cores were also determined and correlated with their indirect tensile strengths. Using analytical methods, the influence of strength and modulus losses on pavement performance was analyzed. As the indirect tensile strength of bituminous mixtures decreases — and consequently, their resilient modulus — the number of load cycles the pavement structure can withstand drops significantly. This article presents the results obtained for pavement service life and equivalent thickness, calculated under specific assumptions, considering the reduction in indirect tensile strength.